The Impact of The Russian-Ukraine Invasion on The Reaction of Asean Stock Markets - Nida, Rahma Sofia; Nafsi, Farichatun; Amelia Putri, Alya Rizka; Andni, Riyan; Johanna, Anne; Jie, Lie; Jixiong, Cai; Wei, Zhang (Journal International Dakwah and Communication, 2023)
This research is motivated by the Russian attack on Ukraine that occurred on February 24, 2022, which resulted in instability in the global stock market. This study aims to determine the reaction of the stock market in ASEAN countries to the event of Russia's invasion of Ukraine by comparing the abnormal value of returns before and after the event. Using quantitative methods based on the event study approach, this research was conducted on six ASEAN stock markets, namely Indonesia, Singapore, Vietnam, Malaysia, Philippines, and Thailand with an observation period of 30 days before and after the Russian-Ukrainian invasion. The data analysis techniques used in this study were normality tests and different tests with the Paired Sample T-Test and Wilcoxon Signed Rank Test. The results of the two different tests carried out showed abnormal return values that tended to be positive and insignificant. This means that the stock market reaction of ASEAN countries to the events of Russia's invasion of Ukraine is not so great or the information content is not very strong. In another sense, the announcement of this event does not put pressure on investors on the ASEAN stock market. The results of this study can help investors to see and evaluate the development of the stock market in ASEAN countries. This research can be a consideration for investors to see the resilience of ASEAN stock markets to an event that occurs.